Practical resistance to Cry toxins and efficacy of Vip3Aa in Bt cotton against Helicoverpa zea. Issue 12 (7th September 2022) - Yang, Fei; Kerns, David L.; Little, Nathan; Brown, Sebe A.; Stewart, Scott D.; Catchot, Angus L.; Cook, Donald R.; Gore, Jeffrey; Crow, Whitney D.; Lorenz, Gustav M.; Towles, Tyler; Tabashnik, Bruce E.
Abstract: BACKGROUND: Crops genetically engineered to make insect‐killing proteins from Bacillus thuringiensis (Bt) have revolutionized management of some pests. However, the benefits of such transgenic crops are reduced when pests evolve resistance to Bt toxins. We evaluated resistance to Bt toxins and Bt cotton plants using laboratory bioassays and complementary field trials focusing on Helicoverpa zea, one of the most economically important pests of cotton and other crops in the United States. RESULTS: The data from 235 laboratory bioassays demonstrate resistance to Cry1Ac, Cry1Fa, and Cry2Ab occurred in most of the 95 strains of H. zea derived from Arkansas, Louisiana, Mississippi, Tennessee, and Texas during 2016 to 2021. Complementary field data show efficacy decreased for Bt cotton producing Cry1Ac + Cry1Fa or Cry1Ac + Cry2Ab, but not Cry1Ac + Cry1Fa + Vip3Aa. Moreover, analysis of data paired by field site and year shows higher survival in bioassays was generally associated with lower efficacy of Bt cotton. CONCLUSIONS: The results confirm and extend previous evidence showing widespread practical resistance of H. zea in the United States to the Cry toxins produced by Bt cotton and corn, but not to Vip3Aa. Despite deployment in combination with Cry toxins in Bt crops, Vip3Aa effectively acts as a single toxin against H. zea larvae that are highly resistant to Cry toxins. Furthermore, Vip3Aa adoption is increasing and previous work provided an early warning of field‐evolved resistance. Thus, rigorous resistance management measures are needed to preserve the efficacy of Vip3Aa against this highly adaptable pest. © 2022 Society of Chemical Industry. Abstract : Practical resistance of Helicoverpa zea to crystalline Bacillus thuringiensis (Bt) toxins, but not Vip3Aa, is widespread in the southern United States. Field efficacy of Bt cotton was negatively associated with survival in bioassays (WS: Widestrike, Cry1Ac + Cry1Fa; BG2: Bollgard 2, Cry1Ac + Cry2Ab; WS3: Widestrike 3, Cry1Ac + Cry1Fa + Vip3Aa).